Design and Development of an Early Warning System for Monitoring Rising Water Levels - Adan, Mohamad Aidil; Alias, Afishah (Enhanced Knowledge in Sciences and Technology, 2025)
Floods rank among the most catastrophic natural disasters, inflicting considerable damage to ecosystems, human lives, and infrastructure. This study centres on the design and implementation of an Internet of Things (IoT)-based early warning system for real-time monitoring of rising water levels. The system incorporates an ESP32 microcontroller and an HC-SR04 ultrasonic sensor to quantify the rate of water level elevation, relaying data through the Blynk IoT platform to deliver real-time notifications. The design features durable hardware, effective programming, and an intuitive interface, guaranteeing dependable performance across diverse conditions, including gradual increases and sudden surges in water rise velocity. Thorough testing confirmed the system’s capability to approximately detect and report substantial variations in water rise velocity. Integration with Google Sheets enables effective data recording for trend analysis and decision-making. This cost-effective and scalable system, designed for flood-prone regions, improves disaster preparedness by facilitating prompt responses to swiftly evolving conditions and provides a basis for extensive flood management applications.